Intensifying Experiential Learning with Dynamic Learning Styles in Traditional Classroom - Nazim, Raja; Raja Yaacob, Raja Ahmad Iskandar; Che Mohd Hashim, Azreen Jihan; Hussain, Ibiwani Alias; Roslan, Azreen (Journal of Technical Education and Training, 2019)
Individual learning style diverges from one another, based on preferential perception on different types of information and degree of understanding the information. Learning contents require the focus to the efficiency of accomplishing learning goals, and all processes involved are considered essential. This paper seeks to explore students’ experiential learning in traditional classroom. It also aims at conceiving students’ learning experience through the transformative learning by adopting modern learning in traditional methods. The study was conducted at Universiti Pendidikan Sultan Idris (UPSI), a local public university in Perak, Malaysia. Questionnaires were distributed, using stratified random sampling. Data was collected from 45 technical and vocational students who underwent a module, using traditional method with either engaging or using technological techniques in classroom. Results indicated that students’ preference in learning were the learning style with comprehension of learning elements and new pedagogical tools in classroom. The results would also assist educators in strategizing teaching and learning in schools or higher learning institutions with no technological facilities to deliver effective learning. The pace of worldwide education development has been highlighted specifically on the role of the educator in exploring students’ capability by uncovering their learning style strengths and opportunities even though in traditional ways